Integrating Inquiry-Based Learning and Cognitive Conflict Strategies to Enhance Critical Thinking in Undergraduate Physics Education - Asy'ari, Muhammad; Muhali, M. (Multi Discere Journal, 2023)
This research aimed to develop and evaluate an instructional device that integrates inquiry-based learning (IBL) with cognitive conflict strategies to enhance students’ critical thinking skills in the topic of fluid mechanics. Employing the 4D development model—Define, Design, Develop, and Disseminate—the study involved 24 undergraduate students enrolled in a physics education program at Universitas Pendidikan Mandalika. The instructional device included syllabi, lesson plans, student worksheets (LKM), handbooks, and a critical thinking assessment instrument. Expert validation indicated high content and structural validity, with LKM and the assessment tool receiving the highest ratings (average score = 3.6). Classroom observations showed high implementation feasibility, particularly in the phases of cognitive conflict presentation and reflective discussion (average score = 3.6). Student learning outcomes were measured through pre- and post-tests, analyzed using Normalized Gain (N-Gain) and paired-sample t-tests. Results demonstrated a statistically significant improvement in critical thinking (average N-Gain = 0.58, t = 25.82, p < 0.0001). Student responses were overwhelmingly positive, and noted barriers such as initial confusion with the LKM format and time constraints were manageable. This study contributes a validated and adaptable model for fostering critical thinking through the synergistic application of inquiry learning and cognitive conflict, grounded in constructivist and conceptual change theory. The device holds promise for broader application across STEM disciplines in higher education.